2020
DOI: 10.2337/db20-0856
|View full text |Cite
|
Sign up to set email alerts
|

Defective FXR-SHP Regulation in Obesity Aberrantly Increases miR-802 Expression, Promoting Insulin Resistance and Fatty Liver

Abstract: Aberrantly elevated expression in obesity of microRNAs (miRNAs), including the miRNA miR-802, contributes to obesity-associated metabolic complications, but the mechanisms underlying the elevated expression are unclear. Farnesoid X receptor (FXR), a key regulator of hepatic energy metabolism, has potential for treatment of obesity-related diseases. We examined whether a nuclear receptor cascade involving FXR and FXR-induced small heterodimer partner (SHP) regulates expression of miR-802 to maintain glucose and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 46 publications
1
30
0
Order By: Relevance
“…MiR-802 levels are increased in obesity [ 10 , 11 , 15 ], where hepatic AMPK activity is low [ 23 , 26 ]. We, thus, examined whether the miR-802 has a role in decreased AMPK function in obesity.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…MiR-802 levels are increased in obesity [ 10 , 11 , 15 ], where hepatic AMPK activity is low [ 23 , 26 ]. We, thus, examined whether the miR-802 has a role in decreased AMPK function in obesity.…”
Section: Resultsmentioning
confidence: 99%
“…Primary mouse hepatocytes (PMH) were isolated as described previously [ 15 , [32] , [33] , [34] ]. Isolated hepatocytes were transfected with 5–50 nM pre-miR-802, antisense-miR-802, or siRNA for Ampkβ1 (ON-TARGETplus SMART pool, Dharmacon), and 2 days later, cells were harvested.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…FXR-SHP axis is closely associated with bile acid and lipid metabolism and represents a promising target for treating NAFLD. New evidence has shown that miR-802-mediated defective FXR-SHP regulation promotes insulin resistance and the development of fatty liver [ 204 , 259 ]. However, the expression level of FXR, but not SHP, was decreased in the liver tissue of patients with NAFLD [ 260 ].…”
Section: Transcriptional Regulation Of Lipid Metabolism By Nrs In Nafldmentioning
confidence: 99%